Implementation of the Drill Method in Learning Arabic with a Communicative Approach - Muhammad Zikran Adam; Laily Fitriani (Journal of Arabic Language Learning and Teaching (JALLT), 2023)
This paper will discuss implementing the drill/practice method for learning Arabic with a communicative approach. This study uses a descriptive qualitative. The subjects of this research were all 7G class students at MTs Negeri Kota Batu. The data collected is in the form of the latest learning information data, the number of students, and data on the implementation of learning methods. Data collection using interview techniques, observation, and documentation. Data analysis was carried out according to the theory of Miles and Huberman, with the stages of data collection, data reduction, data presentation, and conclusions. The result indicates that the drill method with a communicative approach is implemented through three steps. Firstly, the planning stage involves preparing a learning program plan. Secondly, the implementation stage applies the drill method based on the characteristics of the communicative approach. Lastly, the evaluation phase employs formative evaluation techniques. The study identifies four supporting factors for the method's application: student participation, cognitive abilities, clarity of instruction, and availability of learning facilities. This study provides valuable insights and knowledge to improve Arabic language teaching for teachers and researchers to develop additional learning on more functional skills.